The development of a remuneration system for the oil and gas sector - Бейсенбаева A. (Journal of Economic Research & Business Administration, 2017)
Today, the grading system is the best and the only justifiable system of calculating salaries, which allows to clean with basic pay. That is, the grading system allows you to “align” wages and the business logic, and untie the knot of problems related to motivation of the staff of the oil and gas sector. Grading is regarded as a technology to attract and retain highly qualified personnel in the industry. Presents the main stages of building of the process of grading. Shows the main benefits and risks of the remuneration system on the basis of grading. Focused on the fact that the process of grading does not end at the stage of development and implementation. In the subsequent years of system operation is necessary to continuously undertake measures for its control, correction and verification of the adequacy along with the changing conditions of the labour market. Development of grades requires a lot of time and material investments, but with the right approach, the organization obtains a tool that unites all the main systems of personnel management – remuneration, motivation, evaluation and training. The article presents in summary form the recommendations of practitioners the introduction of grading in the organization of the oil and gas sector.